Genetic Diversity of the Cichlid Andinoacara latifrons (Steindachner, 1878) as a Conservation Strategy in Different Colombian Basins - De la Ossa-Guerra, Luz Elena; Santos, Mateus Henrique; Artoni, Roberto Ferreira (Frontiers in Genetics, 2020)
Cichlids constitute a diverse monophyletic group that have developed adaptive strategies to thrive in diverse environments. Andinoacara represents an example of diversification on the South American Andean uplift, providing a key model for understanding the evolution of biogeographic patterns. In this study, we analyzed the species A. latifrons using two mitochondrial markers (COI, cytb) and one nuclear marker (RAG1) in a populational level. Sequences were obtained through tissue collection and from the GenBank database. Populational analysis showed significant structuration among populations, also corroborated with population pairwise Fst results. Fu’s Fs and Tajima’s D results showed populations that seems to be under populational expansion. We identified 22 haplotypes using cytb. The population associations in the Cauca haplotype are related to the Momposina depression and the mixture of the Cauca-Magdalena river basins in the lower Cauca-Magdalena region. We constructed a new phylogenetic tree, which grouped mainly two A. latifrons lineages: (1) an upper Magdalena and Catatumbo clade and (2) an upper Cauca and upper Magdalena clade. Thus, A. latifrons represents a diverse entity that contributes to our understanding of the evolutionary history of northern South America. Our findings provide insight into devising public policies in determining refuges for the preservation of biodiversity in the lower Cauca and Magdalena regions in Colombia.